If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + -1y = -8 Solving -2 + -1y = -8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1y = -8 + 2 Combine like terms: -2 + 2 = 0 0 + -1y = -8 + 2 -1y = -8 + 2 Combine like terms: -8 + 2 = -6 -1y = -6 Divide each side by '-1'. y = 6 Simplifying y = 6
| 8(4x-8)=4(8x+7) | | log(x-3)+log(x-1)=log(3x-7) | | x(x+9)=4x+6 | | 40x^2-23x-30= | | -3(-7v+3)+8v=5v-r | | 8(2q-4)+5(q+11)=65 | | 24x^2+2x-15= | | 8y-7(1)+3=-4(1)+5y-9 | | x=50-(10/3)y | | (7x+8)+(x-22)=2 | | 2x=5x-180 | | 5x^2=11x+36 | | 3b-0.9=4b | | 4cos^4x-5cos^2x+1=0 | | -8y+8=-80 | | 81+99.4= | | 2(n+4)=7n-1 | | 9(13.6)-23= | | x-10=22.36 | | 12+4x=48 | | 3y+3y=5y+1 | | 5(13.6)+13= | | 6-4x=6x-8+4+2 | | 10uv^2(3u-v)+12u^2v(v-3u)= | | -4w^2+8w+5=0 | | (3x)-(4y)=(12) | | 4x=13x-21 | | f(x)=-0.25x^4+2.25x^2+x-3 | | -4(2x-6)-12x=-6 | | 0=6x^2+30x-84 | | 50-6x=10-10x | | 4y+2x=11 |